Artificial intelligence and computer-mediated communication: the text analysis and undergrad's class observation - Prateet Baskota; Tikaram Poudel (Springer, 2024)
Abstract The term "computer-mediated communication" (CMC) describes the transmission of messages and information using computer technology. With the extensive use of email, instant messaging, social media, and other digital platforms in Nepal in recent years, this style of communication has grown in popularity. The article examines how computer-mediated communication (CMC) and artificial intelligence (AI) have grown in significance in Nepal's undergrad English education. This article allows students to collaborate on projects and tasks, which improves their learning experience, by examining the potential of AI and CMC. The facts of Nepal's education have been examined using the four different basic literature reviews. Despite the need for further literature on artificial intelligence and computer-mediated communication in Nepal's English classes for undergrads between 2018 and 2023, the studies reviewed shed light on the possibilities of technology and AI in language acquisition. Undergraduate class observation, self-administered text analysis, social information processing theory and experimental research, which involves adjusting variables to see how they affect learning results, were used to gather data. The study's findings also demonstrate how using CMC platforms encourages students to practice their digital literacy. They gain knowledge on how to move through online spaces, efficiently communicate with a variety of digital tools, and assess the reliability of information sources. Students can communicate with their teachers outside of the classroom via video conferencing software and online discussion boards. This may result in more in-depth discussions and debates as well as greater student engagement.